SUBSURFACE GEOLOGICAL MODEL USING MAGNETIC DATA FOR MOUNT PANDAN AREA, BOJONEGORO REGENCY, EAST JAVA, INDONESIA - Annisa Pardania, Fairuz
Indonesia, especially the island of Java, is located in a volcanic arc zone or known as the ring of fire as evidenced by the presence of many volcanoes, both dormant and active. One of the volcanoes on the island of Java is Mount Pandan. Some facts from Mount Pandan are that there has been a 4.2 SR earthquake around Pohulung Hamlet and there are 90 MWe of geothermal reserves. The research objective in this final project is to model the subsurface image using geomagnetic 2.5D forward modeling. 2.5 D forward modeling which would be used as a reference and to validate the results of the 3D geomagnetic inversion subsurface image test. The 3D geomagnetic inversion test was carried out to obtain the 3D susceptibility of the distribution using MAG3D software. This study uses data in the form of total magnetic anomaly data for the Gunung Pandan area in 2020. The regional and residual anomalies have been separated from the magnetic anomaly data. Furthermore, residual anomaly data supported by geological data and other supporting data are used for 2.5D forward modeling and 3D inversion modeling. The results of 2.5D forward modeling are used as a reference for making reference models in the 3D inversion modeling process. Meanwhile, from the results of 3D inversion modeling, the density distribution is obtained in 3D with the validation of the 2.5D forward modeling model. iv Geomagnetic 3D inversion modeling was tested on 5 parameters: mode, depth weighing, wavelet compression, reference model, and alpha. Parameters that can image the susceptibility distribution according to the reference model are chi fact mode with a value of 1, depth weighting-depth with exponent values of 1 and 0.5, wavelet compression-user with a threshold value of 0.04, reference model, and alpha with a value of 0.01. Based on the results of 2.5D forward modeling and 3D inversion modeling, it can be identified the presence of several intrusions on the modeled trajectory around the area of Mount Pandan that extends to the north. In addition, a fault structure with an almost north-south direction can be identified, and a low magnetic anomaly can be identified with the presence of geothermal manifestations in the northeastern part of the study area